Laparoscopic proximal gastrectomy with hinged double flap method using knotless barbed absorbable sutures: A case series. (2018) - Saeki, Yoshihiro; Tanabe, Kazuaki; Yamamoto, Yuji; Ohta, Hiroshi; Saito, Ryusuke; Ohdan, Hideki
Highlights: Laparoscopic proximal gastrectomy with hinged double flap method is technically challenging. The V-Loc™ 180 wound closure device (V-Loc; Covidien, Mansﬁeld, MA, USA) is useful for intracoporeal reconstruction. The use of V-Loc is safe and produce reproducible results for esophagogastrostomy closure using the hinged double ﬂap method. Abstract: Background: Intracorporeal reconstruction following laparoscopic proximal gastrectomy is technically challenging. The aim of this study was to investigate the use of knotless barbed absorbable sutures in esophagogastrostomy closure using the hinged double ﬂap method. Design & method: The subjects comprised patients with gastric cancer who were scheduled to undergo laparoscopic proximal gastrectomy. The V-Loc™ 180 wound closure device (V-Loc; Covidien, Mansﬁeld, MA, USA) was used for all laparoscopic esophagogastrostomy closures. Between January 2015 and November 2016, 13 patients were enrolled. Results: The mean suturing time was 109.6 min. Median hospital stay was 14 days. One anastomotic minor leakage occurred in an esophagogastrostomy and it was managed conservatively. Twelve of 13 patients did not exhibit any symptoms of reflux esophagitis. Conclusion: These results suggest the use of the unidirectional barbed absorbable suture is safe and produce reproducible results for esophagogastrostomy closure using the hinged double ﬂap method.